2010
DOI: 10.1128/cvi.00082-10
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of a Recombinant Nonglycosylated Erythrocyte Binding Antigen 175 Region II Malaria Vaccine in Healthy Adults Living in an Area Where Malaria Is Not Endemic

Abstract: Erythrocyte binding antigen region II (EBA-175) is a conserved antigen of Plasmodium falciparum that is involved in binding of the parasite to the host's erythrocytes. We evaluated the safety and immunogenicity of a recombinant EBA-175 vaccine with aluminum phosphate adjuvant in healthy young adults living in the United States. Eighteen subjects/group received ascending doses (5, 20, 80, or 160 g) of the vaccine at 0, 1, and 6 months; 8 subjects received placebo. Most of the injection site and systemic reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 42 publications
4
61
0
2
Order By: Relevance
“…On the other hand, EBA-175 RII (where cHABPs 1779 and 1783 are located) is recognised by antibodies in individuals having naturally acquired immunity in an age-dependent manner and inhibits invasion of P. falciparum clinical isolates to some degree (Okenu et al, 2000;El Sahly et al, 2010;Badiane et al, 2013;Irani et al, 2015). High-titre antibodies against EBA-175 RII are associated with protection from clinical malaria in children (Okenu et al, 2000;McCarra et al, 2011), although such association is not clear in some studies or has not been observed in groups having low incidence of disease (Osier et al, 2008;Richards et al, 2010) It has been suggested that EBA-175 RII polymorphism has shown immune selection aimed at maintaining genetic diversity in parasite populations.…”
Section: Antibody Reactivity From Individuals Living In Endemic Areasmentioning
confidence: 99%
“…On the other hand, EBA-175 RII (where cHABPs 1779 and 1783 are located) is recognised by antibodies in individuals having naturally acquired immunity in an age-dependent manner and inhibits invasion of P. falciparum clinical isolates to some degree (Okenu et al, 2000;El Sahly et al, 2010;Badiane et al, 2013;Irani et al, 2015). High-titre antibodies against EBA-175 RII are associated with protection from clinical malaria in children (Okenu et al, 2000;McCarra et al, 2011), although such association is not clear in some studies or has not been observed in groups having low incidence of disease (Osier et al, 2008;Richards et al, 2010) It has been suggested that EBA-175 RII polymorphism has shown immune selection aimed at maintaining genetic diversity in parasite populations.…”
Section: Antibody Reactivity From Individuals Living In Endemic Areasmentioning
confidence: 99%
“…EBA175-RII is a target for invasion inhibitory antibodies [17-21] and the EBA175-GypA interaction is a major RBC invasion pathway [19]. It has also become a leading malaria vaccine candidate [22,23], thus immunogenic epitopes within EBA175-RII should be exploited as potential vaccine candidates.…”
Section: Figurementioning
confidence: 99%
“…The crystal structure of EBA175-RII showing (A) the overlap between the predicted CD8+ epitope (aa 553-561) and the glycan binding sites at residues Lys-553 and Met-554, (B) the overlap between the predicted CD4+ epitope (aa 440-456) and the glycan binding sites at residue Asp-442, (C) the overlap between the predicted BCE (aa [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and the glycan binding sites at residues Lys-28, Asn-29, Arg-31, Ser-32 and Asn-33, (D) the overlap between the predicted BCE (aa 420-440) and the glycan binding sites at residue Lys-439 and (E) the overlap between the predicted BCE (aa 528-547) and the glycan binding sites at residues Gln-542 and Tyr-546.…”
Section: Figurementioning
confidence: 99%
“…The analysis of sera from malaria-endemic areas for the presence of EBA-175 specific antibodies revealed some association with protection in children that have higher antibody titers (reviewed in (Fowkes et al, 2010)). Recently, an EBA-175 based vaccine yielded some clinical efficacy (El Sahly et al, 2010).…”
Section: Antigens Within Merozoite Organellesmentioning
confidence: 99%